Pengaruh brisk walking exercise terhadap kualitas tidur pada pasien diabetes melitus tipe-2 - Rahmat, Fauziah Amanda; Rahmi, Upik; Salasa, Sehabudin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Sleep quality disturbance is a common problem among patients with type 2 diabetes mellitus and is associated with poor glycemic control and decreased quality of life. Physical activity, particularly moderate-intensity exercise such as brisk walking, is considered a simple non-pharmacological intervention that may improve sleep quality. However, evidence regarding its effectiveness in primary healthcare settings remains limited. Purpose: To analyze the effect of brisk walking exercise on sleep quality in patients with type 2 diabetes mellitus Method: This study employed a quasi-experimental pretest-posttest design with a control group. Patients with type 2 diabetes mellitus were purposively selected and assigned to intervention and control groups. The intervention group participated in a brisk walking exercise program for 8 weeks (three times per week), while the control group received no intervention. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. Data were analyzed using descriptive statistics, paired t-test or Wilcoxon test, and independent t-test with a significance level of 0.05. Results: The intervention group showed a significant improvement in sleep quality after the brisk walking program, as indicated by a lower mean PSQI score than the control group. Statistical analysis demonstrated a significant difference in posttest sleep quality scores between groups (p < 0.001). Conclusion: Brisk walking exercise significantly improves sleep quality in patients with type 2 diabetes mellitus. This finding supports the role of structured physical activity as an effective non-pharmacological approach to improving sleep quality in patients with diabetes. Suggestion: Future research is recommended to develop designs with longer intervention durations, larger sample sizes, and involving more diverse populations to increase the generalizability of the findings. Furthermore, the use of objective measures of sleep quality, such as actigraphy or polysomnography, should be considered to complement the subjective measures of the PSQI and minimize potential response bias. Keywords: Brisk Walking Exercise; Sleep Quality; Type 2 Diabetes Mellitus. Pendahuluan: Gangguan kualitas tidur merupakan masalah yang sering dialami oleh pasien diabetes melitus tipe 2 dan berhubungan dengan kontrol glikemik yang buruk serta penurunan kualitas hidup. Aktivitas fisik aerobik intensitas sedang, seperti brisk walking exercise, merupakan intervensi nonfarmakologis sederhana yang berpotensi memperbaiki kualitas tidur. Namun, bukti empiris penerapannya di layanan kesehatan primer masih terbatas. Tujuan: Untuk menganalisis pengaruh brisk walking exercise terhadap kualitas tidur pada pasien diabetes melitus tipe 2. Metode: Penelitian ini menggunakan desain kuasi-eksperimen pretest-posttest dengan kelompok kontrol. Sampel pasien diabetes melitus tipe 2 dipilih secara purposive sampling dan dibagi menjadi kelompok intervensi dan kontrol. Kelompok intervensi menjalani brisk walking exercise selama 8 minggu (3 kali/minggu), sedangkan kelompok kontrol tidak menerima perlakuan. Kualitas tidur diukur menggunakan Pittsburgh Sleep Quality Index (PSQI) sebelum dan sesudah intervensi. Data dianalisis menggunakan analisis deskriptif, uji paired t-test atau Wilcoxon, serta independent t-test dengan tingkat kemaknaan 0.05. Hasil: Terdapat peningkatan kualitas tidur yang bermakna pada kelompok intervensi setelah pemberian brisk walking exercise. Perbandingan skor PSQI posttest antara kelompok intervensi dan kontrol menunjukkan perbedaan yang signifikan secara statistik (p < 0.001). Simpulan: Brisk walking exercise berpengaruh signifikan terhadap peningkatan kualitas tidur pada pasien diabetes melitus tipe 2. Intervensi ini dapat dipertimbangkan sebagai pendekatan keperawatan nonfarmakologis yang efektif dan aplikatif dalam meningkatkan kualitas tidur pasien diabetes di layanan kesehatan primer. Saran: Penelitian selanjutnya disarankan untuk mengembangkan desain dengan durasi intervensi yang lebih panjang, jumlah sampel yang lebih besar, serta melibatkan populasi yang lebih beragam untuk meningkatkan generalisasi temuan. Selain itu, penggunaan alat ukur objektif kualitas tidur seperti actigraphy atau polysomnography perlu dipertimbangkan guna melengkapi pengukuran subjektif PSQI dan meminimalkan potensi bias respon. Kata Kunci: Brisk Walking Exercise; Diabetes Mellitus Type 2; Kualitas Tidur.